Humanitarian confinement: an ethnography of reception centres for asylum seekers at Europe's southern border. (2015) - Campesi, Giuseppe
This article presents the results of an empirical research carried out within Italian reception centres for asylum seekers. The article shows how reception centres can become a trap from which asylum seekers are no longer able to escape as they become victims of a process of social disempowerment making them dependent on the 'humanitarian government'. This reproduction of dependence enables the reception system to carry out a subtle social control function, achieving the effect of confining asylum seekers within a concentrated place that can easily be controlled by the police. But this form of control is exercised even though the law does not provide any explicitly repressive means for keeping them under surveillance. So-called reception centres exert a centripetal force which is hard to resist, and which in a sense has an ability to trap asylum seekers more than any wall. The Italian reception system amounts to a form of 'humanitarian confinement', in that provide hospitality for asylum seekers, while subjecting them to a form of control enacted through humanitarian agents.